Using Tax Incentives to Support Thermal Retrofits in Germany - Karsten Neuhoff; Hermann Amecke; Alexandra Novikova; Kateryna Stelmakh; Jeff Deason; Andrew Hobbes (Climate Policy Initiative, 2011)
The German government has committed to reducing the primary energy demand of buildings by 80% by 2050 and to attaining a thermal retrofit rate of 2%. Achieving both goals will require deep thermal retrofits across the existing building stock. To meet this challenge, the government is exploring what role tax support options could play in encouraging thermal retrofits and ensuring that they deliver the necessary energy performance. The following options are being discussed: - Allow for the accelerated depreciation of investments in the thermal energy efficiency of buildings (further development of 82a EStDV). For commercial owners and landlords, the net present value and the visibility of tax benefits would increase, thus increasing incentives for improving energy efficiency and compensating for the difficulties involved in passing investment costs to users. For private households, thermal retrofit costs could be made deductible as "special expenditures" and tax benefits would increase with the marginal income tax rate. - Offer tax credits. Currently, 20% of up to 6000 Euro in labor costs can be deducted from tax liability (35a German Income Tax Act, EStG). Expanding the volume and the types of qualifying deductions to cover material costs, and increasing the deductible share of the retrofit costs, could support thermal retrofits of owner-occupied buildings. In this paper, we evaluate international (Italy, Netherlands, and U.S.) experiences with tax benefits supporting thermal retrofits and draw upon the experience of the German KfW loans and grants program.
Keywords: H31; R38; Q48; 330; thermal retrofit; tax credits; Energy efficient building; Tax incentive